2020
DOI: 10.5194/angeo-38-983-2020
|View full text |Cite
|
Sign up to set email alerts
|

Induced currents due to 3D ground conductivity play a major role in the interpretation of geomagnetic variations

Abstract: Abstract. Geomagnetically induced currents (GICs) are directly described by ground electric fields, but estimating them is time-consuming and requires knowledge of the ionospheric currents and the three-dimensional (3D) distribution of the electrical conductivity of the Earth. The time derivative of the horizontal component of the ground magnetic field (dH∕dt) is closely related to the electric field via Faraday's law and provides a convenient proxy for the GIC risk. However, forecasting dH∕dt still remains a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 54 publications
3
60
0
Order By: Relevance
“…In this study the goal is to compare the results from multiple SWMF runs, so the conclusions should be unaffected. Nevertheless, it may be important for readers and future studies to mention that Juusola et al (2020) have recently shown, using IMAGE magnetometer data, that the horizontal dB/dt is dominated by telluric currents nearly at all IMAGE stations. This means that much of the spatial and temporal structure seen in the total measured dB/dt comes from underground.…”
Section: Telluric Effectsmentioning
confidence: 98%
“…In this study the goal is to compare the results from multiple SWMF runs, so the conclusions should be unaffected. Nevertheless, it may be important for readers and future studies to mention that Juusola et al (2020) have recently shown, using IMAGE magnetometer data, that the horizontal dB/dt is dominated by telluric currents nearly at all IMAGE stations. This means that much of the spatial and temporal structure seen in the total measured dB/dt comes from underground.…”
Section: Telluric Effectsmentioning
confidence: 98%
“…Using the the Swarm data in the substorm context provided by SuperMAG will enable this study to focus on the substorm time DF currents. Swarm also provides a different view of the currents compared to ground based magnetometers as the latitudinal coverage of the auroral oval crossing is not dependent on the network density and the effect of ground induced currents to the magnetometer measurements, which can sum up to tens of percents of the total field strength at ground level (Juusola et al (2020)), is subdued at Swarm altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of the SECS technique, it is possible to separate the measured magnetic field into external and internal parts, which are represented by two equivalent sheet currents placed in the ionosphere and underground (Juusola et al, 2020).…”
Section: Construction Of the Source Using The Secs Methodsmentioning
confidence: 99%
“…Two models approximate the source by a laterally varying sheet current flowing above the Earth's surface. One of the models is built using the results of physics-based 3-D MHD simulation of the near-Earth space, another model uses the IMAGE magnetometer data and the Spherical Elementary Current Systems (SECS) method (Juusola et al, 2020;. The third modeling is based on a "plane wave" approximation which assumes that the source is locally laterally uniform.…”
Section: Space Weathermentioning
confidence: 99%